Remodeling of rat ventral prostate after castration involves heparanase-1 - Augusto, Taize M.; Felisbino, Sergio L. [UNESP]; Carvalho, Hernandes F. (Springer, 2008)
Androgen deprivation causes the rat ventral prostate to reduce to 10% of its original size by 21 days after castration. The regressive changes result from the loss of epithelial cells by apoptosis and marked reorganization of the stroma. We have investigated whether these changes are accompanied by variations in heparanase expression. The ventral prostate of castrated rats was collected and processed for the quantification of heparan sulfate (HS), for the measurement of heparanase expression and its localization by reverse transcription/polymerase chain reaction, Western blotting, and immunohistochemistry, and for transmission electron microscopy (TEM). Absolute HS content decreased significantly as early as day 7 after surgery. Heparanase mRNA peaked 7 days after castration. The heparanase proenzyme (65 kDa) and the active form (50 kDa) were identified and peaked on day 7 after castration; this coincided with maximum HS-degrading activity. Heparanase was located to the basolateral surface of epithelial cells and in the adjacent stroma. After castration, staining for heparanase was reduced in the epithelium and increased in the stroma. TEM revealed that the peak of heparanase expression at day 7 after castration was associated with extensive changes in the basement membrane of the epithelium, endothelium and smooth muscle cells involving cell shrinkage and/or deletion by apoptosis. These results suggest that heparanase expression increases after castration and correlates with a decreased amount of HS. This variation in heparanase expression is involved in tissue remodeling and in the control of the regressive pattern after 1 week of androgen deprivation.
Keywords: basement membrane; castration; heparanase; heparan sulfate; prostate; rat (Wistar)